2014
DOI: 10.1186/1866-1955-6-42
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal glutamate-glutamine (Glx) in adults with Down syndrome: a preliminary study using in vivo proton magnetic resonance spectroscopy (1H MRS)

Abstract: BackgroundDown syndrome (DS), or trisomy 21, is one of the most common autosomal mutations. People with DS have intellectual disability (ID) and are at significantly increased risk of developing Alzheimer’s disease (AD). The biological associates of both ID and AD in DS are poorly understood, but glutamate has been proposed to play a key role. In non-DS populations, glutamate is essential to learning and memory and glutamate-mediated excitotoxicity has been implicated in AD. However, the concentration of hippo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…In DS, decreased NAA and increased MI have been observed in the hippocampus of adults by MRS ( Beacher et al, 2005 , Lamar et al, 2011 ) and in an early report of one individual with DS in the posterior parietal cortex (PCC) ( Shonk et al, 1995 ). Interestingly, in a larger study using MRS in people with DS with and without dementia, hippocampal measures of Glx did not distinguish these two groups, and neither was different from controls ( Tan et al, 2014 ).In this study, we hypothesized that signatures of neuronal health would be reduced, and those of inflammation increased in DS as a function of cognitive status particularly in the PCC as it is a region where hypometabolism is observed in adults with DS ( Haier et al, 2003 ). Our long-term goal is to develop in vivo 1 H-MRS criteria for future clinical settings that enable early identification of neurochemical differences, prediction of dementia development, and consequently treatment efficacy, in adults with DS.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…In DS, decreased NAA and increased MI have been observed in the hippocampus of adults by MRS ( Beacher et al, 2005 , Lamar et al, 2011 ) and in an early report of one individual with DS in the posterior parietal cortex (PCC) ( Shonk et al, 1995 ). Interestingly, in a larger study using MRS in people with DS with and without dementia, hippocampal measures of Glx did not distinguish these two groups, and neither was different from controls ( Tan et al, 2014 ).In this study, we hypothesized that signatures of neuronal health would be reduced, and those of inflammation increased in DS as a function of cognitive status particularly in the PCC as it is a region where hypometabolism is observed in adults with DS ( Haier et al, 2003 ). Our long-term goal is to develop in vivo 1 H-MRS criteria for future clinical settings that enable early identification of neurochemical differences, prediction of dementia development, and consequently treatment efficacy, in adults with DS.…”
Section: Introductionmentioning
confidence: 77%
“…Decreased NAA and increased MI have also been observed in the hippocampus of DS adults by MRS ( Beacher et al, 2005 , Lamar et al, 2011 ) and in an early report of one individual with DS in the PCC ( Shonk et al, 1995 ). In people with DS with and without dementia, hippocampal measures of Glx did not distinguish these two groups, and neither was different from controls ( Tan et al, 2014 ). In this study, we chose a priori to do the measurements in PCC because PCC demonstrates early metabolic deficits and astrocytic inflammation in AD ( Leech and Sharp, 2014 , Minoshima et al, 1997 ) and may provide a more reliable set of measures as it is less sensitive to head movement.…”
Section: Discussionmentioning
confidence: 95%
“…Decreased NAA and increased MI is observed relatively consistently across studies in non-demented adults with DS compared with age matched non-DS controls (Shonk and Ross, 1995 ; Berry et al, 1999 ; Huang et al, 1999 ; Beacher et al, 2005 ; Lamar et al, 2011 ; Lin et al, 2016 ) with a few exceptions (Murata et al, 1993 ; Smigielska-Kuzia et al, 2010 ). Hippocampal Glx was not different in people with DS from controls (Tan et al, 2014 ). It may not be surprising that MI levels are generally higher in people with DS as the MI cotransporter (SLC5A3) gene is on chromosome 21 and is overexpressed in DS (Berry et al, 1995 ).…”
Section: Metabolic Imaging Biomarkers—mrsmentioning
confidence: 99%
“…Contradictory observations have been reported regarding the level of glutamate in DS: some post-mortem studies found no difference in glutamate or glutamine concentrations in the frontal lobes of foetal DS brains ( Whittle et al, 2007 ), while others reported decreased levels in the hippocampus or unchanged levels in temporal and frontal lobe of adult DS subjects ( Reynolds and Warner, 1988 , Risser et al, 1997 , Seidl et al, 2001 ). A more recent study found no significant difference in hippocampal glutamate-glutamine levels between adult DS subjects and controls ( Tan et al, 2014 ), using in vivo proton magnetic resonance spectroscopy to overcome the limitations deriving from post-mortem analysis of neurotransmitters. This suggests that glutamate levels do not account for the cognitive impairment in DS.…”
Section: Down Syndromementioning
confidence: 99%